2021
DOI: 10.1007/s10570-021-04287-7
|View full text |Cite
|
Sign up to set email alerts
|

Poly ɛ-caprolactone/nanostarch composite nanofibrous wound dressing with antibacterial property and pH stimulus drug release

Abstract: Chronic wound infections pose a major threat in wound care management. Recently, many functional materials have been introduced, to fabricate wound dressings. These wound dressing materials not only cover the wound but also facilitate its healing process. In this study, a novel nanostarch (NS) laden composite nanofibrous membrane of PCL was developed for wound dressing. Electrospun membrane loaded with 25 wt% NS (25NS@PCL), showed an average fiber diameter of 175 ± 37 nm with enhanced hydrophilicity, water upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…pH-Responsive hydrogels are the main type of pH-responsive wound dressings. Other advanced pH-responsive materials include nanofibers, 96 composite films, 97 nanoparticle clusters, 98 and microneedles, 99 each with unique characteristics and advantages for wound healing. In this section, the pH-responsive mechanisms and properties of other pH-responsive materials are discussed, and the relevant information is summarized in Table 2.…”
Section: Other Types Of Ph-responsive Wound Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…pH-Responsive hydrogels are the main type of pH-responsive wound dressings. Other advanced pH-responsive materials include nanofibers, 96 composite films, 97 nanoparticle clusters, 98 and microneedles, 99 each with unique characteristics and advantages for wound healing. In this section, the pH-responsive mechanisms and properties of other pH-responsive materials are discussed, and the relevant information is summarized in Table 2.…”
Section: Other Types Of Ph-responsive Wound Dressingsmentioning
confidence: 99%
“…In addition, 15 days of long-acting antimicrobial activity demonstrated an excellent controlled release effect. 96 Electrospinning technology could realize intelligent drug delivery by adjusting of composition ratio. Liu et al develop CS/ PVA/GO nanofibrous membranes with strong antibacterial activity and sustained-release properties.…”
Section: Other Types Of Ph-responsive Wound Dressingsmentioning
confidence: 99%
“…However, it has been reported that this can be overcome by using extracted cellulose from different plants from Ecuador [69]. Cellulose has been widely used to produce polymers for tissue engineering applications and skin regeneration, including but not limited to hydrogels [69][70][71][72], films [73], nanofibrous wound dressing [74], non-woven composites [75], 3D-printed scaffolds [76], and fiber bats [77] among others.…”
Section: Cellulosementioning
confidence: 99%
“…Antibacterial poly ɛ‐caprolactone/nanostarch composite nanofibrous wound dressing with pH stimulation drug release was reported by Reshmi et al. [ 182 ] The membrane was shown to have strong cell proliferation, low coagulation characteristics, and good blood compatibility. This membrane also exhibited pH stimuli drug (gentamicin) releasing activity as well as diffusion‐controlled release kinetics.…”
Section: Nanostarch Based Antimicrobial Polymersmentioning
confidence: 99%